2021
DOI: 10.1126/sciadv.abf0971
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to mitochondrial stress requires CHOP-directed tuning of ISR

Abstract: In response to disturbed mitochondrial gene expression and protein synthesis, an adaptive transcriptional response sharing a signature of the integrated stress response (ISR) is activated. We report an intricate interplay between three transcription factors regulating the mitochondrial stress response: CHOP, C/EBPβ, and ATF4. We show that CHOP acts as a rheostat that attenuates prolonged ISR, prevents unfavorable metabolic alterations, and postpones the onset of mitochondrial cardiomyopathy. Upon mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 76 publications
6
73
0
Order By: Relevance
“…While these adaptive mechanisms could be cardioprotective in the short term, unresolved, chronic ISR mt could contribute to the pathogenesis of mitochondrial cardiomyopathies by causing metabolic imbalances. In agreement with this hypothesis, ISR mt leads to metabolic imbalance in the heart and muscle with genetic alterations of mtDNA maintenance, transcription, or translation (Dogan et al, 2014;Forsstrom et al, 2019;Kaspar et al, 2021;Khan et al, 2017;Kuhl et al, 2017;Nikkanen et al, 2016). However, the cardiac effects of mutations in mitochondrial proteins not involved in mtDNA functions remain to be elucidated.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…While these adaptive mechanisms could be cardioprotective in the short term, unresolved, chronic ISR mt could contribute to the pathogenesis of mitochondrial cardiomyopathies by causing metabolic imbalances. In agreement with this hypothesis, ISR mt leads to metabolic imbalance in the heart and muscle with genetic alterations of mtDNA maintenance, transcription, or translation (Dogan et al, 2014;Forsstrom et al, 2019;Kaspar et al, 2021;Khan et al, 2017;Kuhl et al, 2017;Nikkanen et al, 2016). However, the cardiac effects of mutations in mitochondrial proteins not involved in mtDNA functions remain to be elucidated.…”
Section: Introductionmentioning
confidence: 76%
“…Abnormalities of cardiac mitochondria arise in genetic diseases associated with alterations of OXPHOS (El-Hattab and Scaglia, 2016). In these diseases, hypertrophic cardiomyopathy and heart failure (Brunel-Guitton et al, 2015) are accompanied by metabolic remodeling (Nakamura and Sadoshima, 2018) suggestive of mitochondrial integrated stress response (ISR mt ) (Dogan et al, 2014;Forsstrom et al, 2019;Kaspar et al, 2021;Khan et al, 2017;Kuhl et al, 2017;Nikkanen et al, 2016). The ISR mt activates the activating transcription factors ATF4 and ATF5, which downregulate the expression of OXPHOS proteins, while upregulating chaperones, proteases, proteasome subunits, and other proteostasis components aimed to reduce proteotoxic stress (Boos et al, 2020;Higuchi-Sanabria et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This observed metabolic adaptation has also been observed in neurons upon mitochondrial toxicity caused by exposure to MMP + or by mutations in PINK1 and PARKIN (Krug et al 2014 , Celardo et al 2017 ). In addition, ATF4 and CHOP signaling without a clear UPR response has been observed in the context of muscle disorder (Kaspar et al 2021 ). Notably, the AAR is also linked to the “integrated stress response”, that restores balance after amino acid starvation and other types of cellular stress and involves ATF4 (Costa-Mattioli and Walter 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of UPR mt is likely more complicated in mammalian cells. Recent studies suggest that three bZIP transcription factors (C/EBP homologous protein [CHOP] and activating transcription factors 4 and 5 [ATF4 and ATF5]) trigger UPR mt activation, which requires the integrated stress response (ISR)-associated phosphorylation of translation initiation factor 2A (eIF2α) by general control non-derepressible 2 (GCN2) and protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK) ( Aldridge et al, 2007 ; Fiorese et al, 2016 ; Fiorese and Haynes, 2017 ; Kaspar et al, 2021 ). A recent study indicated that ATF5 is the mammalian ortholog of ATFS-1 because its activity appears to be regulated by mitochondrial import efficiency ( Fiorese et al, 2016 ).…”
Section: Mitochondrial Quality Controlmentioning
confidence: 99%